2009
DOI: 10.1002/etc.5
|View full text |Cite
|
Sign up to set email alerts
|

Cry1Ab toxin production of MON 810 transgenic maize

Abstract: Levels of Cry1Ab toxin were detected in genetically modified maize of genetic event MON 810 against near isogenic maize as negative control by two commercial immunoassays. The immunoassays were characterized for their cross-reactivity (CR) between Cry1Ab protoxin and activated toxin, and were compared with each other for toxin detection in a reference plant sample. Cry1Ab toxin levels, corrected for active toxin content using the CR values obtained, were monitored in maize DK-440 BTY through the entire vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 32 publications
(28 reference statements)
1
30
3
Order By: Relevance
“…Nevertheless, we noticed that the concentrations of the Cry1Ac protein in rice residues were significantly higher than those reported in our previous study (Xiao et al, 2014), and such difference was also observed in transgenic maize expressing the Cry1Ab protein in three different years (Székács et al, 2010). The variation in the Cry protein expression in Bt crops may be caused by differences in the age of the plant material due to different harvest dates for our two-year experiments and year-to-year climate variation, e.g., temperature and rainfall .…”
Section: Cry1ac Protein Degradationcontrasting
confidence: 72%
“…Nevertheless, we noticed that the concentrations of the Cry1Ac protein in rice residues were significantly higher than those reported in our previous study (Xiao et al, 2014), and such difference was also observed in transgenic maize expressing the Cry1Ab protein in three different years (Székács et al, 2010). The variation in the Cry protein expression in Bt crops may be caused by differences in the age of the plant material due to different harvest dates for our two-year experiments and year-to-year climate variation, e.g., temperature and rainfall .…”
Section: Cry1ac Protein Degradationcontrasting
confidence: 72%
“…The amount of Cry1Ab in leaves of the different transformation events typically ranges from 1 to 17 μg/g fresh weight (FW) (Obrist et al, 2006a; Nguyen and Jehle, 2007; Székács et al, 2010). In contrast, Cry1Ab levels in pollen significantly differ among events.…”
Section: Introductionmentioning
confidence: 99%
“…In MON810 maize, the cry1Ab gene is truncated, and according to the manufacturer, codes for a pre-activated 91-kD truncated rCry1Ab toxin (CERA, 2015). The rCry1Ab toxin is expressed continuously but in different quantities in various tissues in transgenic maize throughout the life cycle of the plant (Székács et al, 2010a), creating a different exposure scenario for nontarget organisms than occurs through either pro-toxin expression by the bacterium itself or as used in pesticidal Bt sprays.…”
mentioning
confidence: 99%